Synthesis, Characteristics and Study the Photoluminscience of the CdSxSe1-x Nanocrystaline Thin Film (Baghdad Science Journal, 2020)
The present work focuses on the changing of the structural characteristics of the grown materials through different material characterization methods. Semiconductor CdSxSe 1-x nano crystallines have been synthesized by chemical vapor depostion. (X- ray Diffraction; XRD), (Field Emission Scanning Electron Microscopy; FESEM), measured the characterization of Semiconductor CdSxSe1-x nano crystallines. The optical properties of semiconductor CdSxSe1-x nanocrystallines have been studied by the photoluminescence (PL) (He-Cd pulsed ultraviolet laser at 325nm excitation wavelength) at room temperature. The results showed the change rule of photoluminsence peak at different S/Se ratios according to the photoluminsence spectral analysis technology. The photuminscence peak can be continuously modulated between (500- 650) nm, so the tunable emission of the materials in the present work have novle applications in the area of bioscience and spectroscopy, etc.